Evaluation of technologies and resources from the spatial and social aspect - Nagy, János; Sinóros-Szabó, Botond (Acta Agraria Debreceniensis, 2014)
The basic functioning of the world is mostly led by negative trends. One of the fundamental reasons for this phenomenon is that the different technologies (hardware, software, resources) do not act properly and in the proper structure by means of the produced products and services. Therefore, the examination of technologies and resources is a key question of our world and development from various aspects. Technologies convey all positive and negative impacts which can be regarded as the fundamental reasons and causes of harmonious or disharmonious development. For this reason, the role of technologies in development and harmonious functioning is of paramount importance.As a final conclusion, we established that the different technologies (hardware, software, resources) are interpreted as impact conveyors which predominate by means of products and services in a way that their relation system is determined. By using the thermodynamic interpretation which is the basis of the functioning of the world, we built a system consisting of 14 elements to evaluate different technologies, to interpret its functioning and to develop positive interactions and trends.